The Jari Project Managed By The Orsa Group:: Corporate Social Responsibility Applied To The Amazon Context (Sustainability in Debate, 2012)
The development of the Jari region, in the Northeastern part of Brazil’s Amazon region, since the middle of the 20th century, ha been intrinsically linked to the evolution of the Jari project, a huge private agro-industrial enterprise aiming at the large-scale production of cellulose. Harshly criticized during the 1970s and 1980s for its ecological impact and waste of human resources, but also due to the lack of economic viability, the project was eventually taken over by a new firm (the Orsa group) after coming close to bankruptcy in 1997. Under Orsa’s management, centered on the concept of corporate social and environmental responsibility (CSR), the Jari project of the XXI century resurrects as an innovative, lucrative and certified firm, pioneer in the application of CSR policies in the Amazon context. This article discusses the manifold strategies developed by the Orsa group and its conveniences and shortcomings for both the firm and the local populations of the Jari region today.